International relations theories in action - Zimmermann, Hubert; Elsinger, Milena; Burckhardt, Alex (Thousand Oaks Sage, 2024)
This original introduction to the field is the most concise, engaging, and readable textbook available. Core problems and cases of international politics are used to introduce theoretical concepts in a way that is both relevant and applied. Theory is not presented in the kind of traditional, abstract manner found in existing texts, or peremptorily summarised with reference to 'Great Debates'. Instead, theory is brought alive through application and concrete historical examples. Not presupposing any prior student knowledge or interest in the "ism's". the text accomplishes this by adopting a critical and questioning approach. It draws on theory as a series of tools to be used, adapted, combined and applied when grappling with some of the most contested issues in global politics. These range from traditional security and economic issues, to challenges of the Anthropocene, global inequality, race and racism, financialization and global health. The textbook aims to enthuse students to move beyond the status of an informed consumer of current affairs, and toward a critical, analytical understanding of IR. With this in mind, this book is designed as an essential companion for all undergraduate students
Keywords: International relations